Changes in Nutritional Status of Hospitalized Patient in a Tertiary Level Hospital - Shawkat Ali, Mohammad; Ali Haider, Salahuddin Mohammed; Mohsin, Mostafa Noor; Hasan, Rafiqul; Hasan, Hamid (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Nutrition is an important health parameter among hospital admitted patients. The objective of our study was to evaluate the changes of nutritional status among the adult patients during hospitalization. Materials and methods: It is prospective observational study done on 100 patients admitted at Medicine ward, CMCH from January 2012 to June 2012. 100. Body Mass Index (BMI) and Mid Arm Circumference (MAC) were compared at the time of admission and at weekly interval and hospital discharge. Data was collected and analyzed by SPSS 20. Results: Among the 100 patients 52(52%) were male and 48(48%) were female.38 (38%) patients had BMI <18.5 Kg/m2 and were malnourished whereas 62 (62%) patients had normal BMI. 25 (25%) patients had malignancy, 22(22%) patients had tuberculosis, 18 (18%) patients had chronic liver disease, 14 (14%) patients had connective tissue disease and 21(21%) patients had other diagnosis. Changes of BMI and MAC were found in Malignancy tuberculosis, chronic liver disease and in connective tissue disease during hospital stay. Among the 25 patients of malignancy on admission they had BMI 20.01 ± 2.86 Kg/m2 which was reduced into 19.22 ± 2.91 Kg/m after 7th day of admission Those patients diagnosed as tuberculosis had BMI 18.19 ± 2.72 Kg/m2 on admission which was changed into 18.34 ± 2.87 Kg/m2 after 7th of admission. Paired t test was done on admission, 7 day and 21st day where significant changes were found in BMI and MAC. No significant changes of MAC and BMI were found at 14th and 21st day of hospital stay. 82(82%) patients had average hospital stay of one week, 16(16%) patients had two weeks and only 2(2%) had three weeks.50 (50%) patients had supplied food from hospital, 6(6%) patients had home made food but 44(44%) patients had both sources. Conclusion: Changes in BMI and MAC in early weeks s of hospital stay was significant among the admitted patients. Disease pattern might also be influenced nutritional changes. JCMCTA 2020 ; 31 (2) : 133-139